Robust Inter‐Hemispheric Asymmetry in the Response to Symmetric Volcanic Forcing in Model Large Ensembles. Issue 9 (10th May 2021) - Pauling, Andrew G.; Bushuk, Mitchell; Bitz, Cecilia M.
Abstract: The climate response to volcanic eruptions in the twentieth century is difficult to separate from the influence of anthropogenic greenhouse gas forcing and internal variability. Here, we make use of recently available large ensembles of Earth‐system model simulations to better understand the forced climate response to contemporary volcanic eruptions. While the Pinatubo eruption in June 1991 resulted in approximately symmetric forcing between the Northern and Southern Hemispheres, the ensemble‐mean simulated temperature and sea ice responses it produces are asymmetric. The strongest cooling and sea ice expansion occur in the Arctic, while the responses in the Antarctic are weak. The damped high‐latitude Southern Hemisphere response to volcanic forcing is analogous to the fast response to increased greenhouse gas concentrations, despite the differing physical nature of the forcing. We find that Arctic cooling in response to a Pinatubo‐scale eruption may not occur due to the high internal variability in that region Plain Language Summary: Volcanic eruptions can have a large short‐term influence on global climate due to the injection of reflective particles into the stratosphere that cool the planet. However, the impact of twentieth century volcanic eruptions on climate has been difficult to distinguish from the impact of other factors such as anthropogenic greenhouse gas forcing and natural variability. Averaging the response over many climate model simulations, each with different natural variations but the same climate, suppresses the influence of natural variability and allows the true response to become more evident. The eruption of Pinatubo in June 1991 spread reflective particles into the stratosphere roughly evenly between the Northern and Southern Hemispheres. However, the changes in temperature and sea ice it produced were quite different between the two hemispheres. The area of Arctic sea ice grew, and the region cooled after the eruption, while the Antarctic showed little response. Previously, this result had only been shown in single climate models with idealized conditions where all forcing except the volcanoes was held fixed. Our results show that this response is a robust feature of the climate response to volcanic eruptions, and is not strongly dependent on the particular climate model used. Key Points: Analysis of model large ensembles shows stronger cooling in the Arctic than in the Antarctic in response to symmetric volcanic forcing Arctic sea ice area and volume increase for several years after the eruption while Antarctic sea ice area and volume show little response The damped Southern Ocean cooling is analogous to the weak warming in the short‐term response to greenhouse gas forcing in that region